2005
DOI: 10.1634/theoncologist.10-5-345
|View full text |Cite
|
Sign up to set email alerts
|

HER1/EGFR Inhibitor-Associated Rash: Future Directions for Management and Investigation Outcomes from the HER1/EGFR Inhibitor Rash Management Forum

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
188
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(204 citation statements)
references
References 34 publications
4
188
0
12
Order By: Relevance
“…Drugs targeting the extracellular domain of the epidermal growth factor receptor (EGFR) (e.g., cetuximab, panitumumab) or its tyrosine kinase (e.g., gefitinib, erlotinib) are in clinical use for the treatment of nonsmall cell lung cancer (NSCLC), pancreatic cancer, and colorectal cancer (CRC) [2][3][4][5]. Although effective, EGFR inhibitors (EGFRIs) are associated with dermatological toxicities.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Drugs targeting the extracellular domain of the epidermal growth factor receptor (EGFR) (e.g., cetuximab, panitumumab) or its tyrosine kinase (e.g., gefitinib, erlotinib) are in clinical use for the treatment of nonsmall cell lung cancer (NSCLC), pancreatic cancer, and colorectal cancer (CRC) [2][3][4][5]. Although effective, EGFR inhibitors (EGFRIs) are associated with dermatological toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials evaluating EGFRIs have reported a range of adverse cutaneous reactions with variable frequencies (Table 1), the most common being papulopustular rash (also referred to as acne or acneiform rash) on the face and upper torso, which occurs in up to 80% of patients [10]. The median onset of EGFRI-related cutaneous toxicity is 1-2 weeks after the initiation of treatment, with a maximum intensity at 2-3 weeks [2]. EGFRIassociated rash may gradually improve or resolve spontaneously while treatment is continued over 2-3 months [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations